Implementing Procurement Management in Nuclear Medicine Installation Using ERP - Amelia Purnama Putri; Ari Yanuar Ridwan; Umar Yunan Kurnia Septo Hediyanto; Kharisma Perdani Kusumahstuti (Jurnal Teknologi Informasi dan Multimedia, 2023)
To support health services at nuclear medicine installations certainly requires various types of goods, ranging from medical devices, radioactive materials, medicines, and various other needs. The right procurement process is key in ensuring the smooth running of quality nuclear medicine installation health services. The process of procurement of goods at nuclear medicine installations in public hospitals is still carried out conventionally and separately between divisions or sections, this can cause communication problems, lack of data integration, and difficulties in monitoring stock and fulfilling requests quickly. Therefore, a system that can manage the procurement of goods is needed. ERP system development using open-source Odoo to support the integrated procurement process using the Quickstart method. The ERP system can facilitate the procurement of goods for nuclear medicine installations in designing systems starting from the bidding process to vendors, purchasing goods, receiving goods to enter the warehouse, to the payment process to vendors. The ERP system will combine business processes and data from various divisions or parts in one centralized database. This integration allows the use of consistent and real time information in decision making, transparency, and data accuracy. The results of this research are in the form of a system design using the ERP purchase module to support the procurement of nuclear medicine installation goods.